Thermomechanical analysis of cold formed steel sections - Mesquita, L.M.R. (2017)
This work presents an experimental study about cold formed steel elements submitted to compression loads. The sections analyzed are C and Z sections made of steel sheet with 1.5 and 2 [mm] thick and three different cross section heights. The compression tests were made at ambient and elevated temperatures. In both cases a pined support was developed and used. The member resistance at ambient temperature was determined by applying an increasing compression load until the member collapse was achieved. The fire tests were performed in a fire resistance furnace, using the same type of end supports, and a mechanical load given by a specific degree of utilization that is maintained constant during the fire test. These tests allow the determination of the fire resistance time and member critical temperature. The experimental results are compared with the ones obtained with the Eurocode simplified models.